Evaluation of Fracture Mechanics Parameters of Light-weight Concrete by Implementing Natural Pumice Stone as Coarse Aggregate - Nimat, Azhar Jawad; Mohammed, Azad Abdulkadir; Mohammed, Ahmed Salih (Sulaimani Journal for Engineering Sciences, 2023)
The concrete material softening response curve is essential for accurate numerical analysis of concrete. The tensile strength, initial fracture energy, and total fracture energy are the three parameters of interest in defining such softening response. Among them, the fracture energy is usually regarded in any analytical program that attempts to model reinforced concrete (RC) structures' behavior. The brittleness and fracture characteristics of lightweight concrete (LWC) produced from 19 mm maximum size natural pumice stone aggregate were investigated via testing notched beam specimens under three-point bending test. Fracture parameters were analyzed and explained using the size effect method (SEM) and the work of fracture method (WFM), and the results were compared to those found in the published literature. The results show mean total fracture energy (GF) of 145.65 N/m and a mean characteristic length (Lch) of 590.34 mm. Later, by correlating the result obtained via this method to the SEM approach, the initial fracture energy (Gf) was determined with a mean value of 58.26 N/m and the fracture toughness (KIC) was found to be 38.47 MPa.mm0.5. Lightweight concrete was found to be more ductile and need more energy to propagate fracture across the specimen, as shown by a comparison of current data to that acquired from literature.
Keywords: Fracture mechanics; Notched beam; Lightweight concrete; Work of fracture method